The difference of bond strength between multi step and self adhesive resin cements in indirect composite restoration - Zakaria, Myrna Nurlatifah; Fadil, Moch. Richata; Armilia, Milly (Padjadjaran Journal of Dentistry, 2010)
Resin based luting cement application generally requires pre-treatment procedure such as etching and adhesive application prior to cementation. This multi-step application technique might compromise bonding alternative effectiveness and is time consuming. An alternative for multi-step resin cement is the self-adhesive resin cement that combines the use of etch, adhesive and cement in one single application. The objective of this study was to compare the bonding effectiveness of the multi-step resin cement and the self-adhesive resin cement using tensile bond strength method towards indirect composite block dentin surface. This study was a true experimental research conducted by in vitro method on 30 flat dentin surfaces created from extracted lower premolars samples. Samples were divided into two groups, each 15 samples for multi-step and self-adhesive resin cements. An indirect composite block (2x2x10 mm) was then cemented to each dentin surface using multi-step resin cement (Rely X ARC, 3M ESPE) or self-adhesive resin cement (Rely X Unicem, 3M ESPE) according to manufactureâs instruction. Samples were storage for 24 hours in saline water and tensile bond strength of each samples were tested using the LRX Plus Lyod Instrument at 1 mm/minute speed. The result of the study concluded that the tensile bond strength of multi-step resin cement towards indirect composite restoration and dentin surface was significantly higher than the self-adhesive resin cement.